ANALISIS PENGARUH FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BEI PERIODE TAHUN 2013-2016 - Luthfiana Sari, 14.05.52.0268; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the effect of profitability, liquidity, firm size, sales growth and asset structure to capital structure. The population in this study are all Real Estate and an Property firms listed in Indosia Stock Exchange year 2013-2016. Sample in this research is taken by using technique of Purposive Sampling so that obtained by sampel counted 41 company. The data analysis tool used in this study is multiple regression analysis. The results of this study indicate that profitability has a positive and significant effect on capital structure, liquidity has a negative and insignificant effect on capital structure, firm size has a significant positive effect on capital structure, sales growth have positive and significant influence to capital structure and asset structure have positive and significant impact to capital structure. Keywords: Profitability, Liquidity, Company Size, Sales Growth, Asset Structure, Capital Structure.